Lung protective effects of budesonide nebulization during perioperative period of thoracolumbar fusion - Li, Wenjing; Zhao, Yu; Sun, Zhijian; Yang, Xu; Zhao, Lijuan; Shen, Jianxiong (Journal of Thoracic Disease, 2014)
Objective: To determine the pulmonary protective effect of budesonide nebulization in patients undergoing spinal fusion for thoracolumbar degenerative disorders. Methods: Forty patients who underwent spinal fusion at our hospital from January 2013 to December 2013 for the treatment of thoracolumbar degenerative disorders were randomly allocated into a budesonide intervention group (budesonide group) and a control group. The control group received routine supportive therapy including rehydration, analgesia, and neurotrophic drug treatment; in addition to these, the budesonide group was administered with budesonide nebulization (1-mg budesonide/2-mL saline, twice daily) from 1 day preoperatively through 3 days postoperatively. Respiratory symptoms, arterial blood gas, and pulmonary complication before and after the operations were observed and compared between the two groups. Results: The patients ranged in age from 46 to 81 years old (mean, 62.4±9.4 years), and comprised 20 men and 20 women. There were no significant differences in postoperative body temperature, heart rate, and respiratory rate between the groups (P>0.05). The change in arterial partial pressure of oxygen (PaO2) from baseline was significantly lower in the budesonide group than in the control group (at 2.4±12.4 vs. 16.0±11.3 mmHg) (P=0.002), so was the findings for oxygen saturation (SpO2) (0.2%±2.3% vs. 2.6%±3.3%), respectively (P=0.047). The incidence of postoperative pulmonary symptoms and complications, such as coughing, shortness of breath, and dyspnea, was 0% in the budesonide group and 15% in the control group; overall, the budesonide group performed better than control group in all pulmonary parameters. None of the patients in the budesonide group experienced severe events associated with glucocorticoid therapy. Conclusions: Perioperative budesonide nebulization may reduce the postoperative pulmonary complications in middle-aged and elderly patients undergoing thoracolumbar fusion to treat thoracolumbar degeneration, with favorable efficacy and safety.